Cognit.ca - About - U15 (Cognit.ca, 2021)
Cognit.ca is a tool for businesses, non-profits, governments and others who want to access the experts, facilities and/or intellectual property that exists on campuses across Canada. Cognit.ca does this by analyzing over 200,000 research projects, hundreds of facilities and more than ten of thousand of pieces of IP to identify the most relevant institutions, researchers, facilities and licensing opportunities for a given search term. COGNIT.CA was originally created by The U15 Group of Canadian Research Universities as part of a larger set of initiatives to increase the impact of Canadian university research. It is now developed in partnership with Universities Canada, collaboration with the Canada Foundation for Innovation (CFI) and with the support of the Canadian Institutes of Health Research (CIHR), the Natural Sciences and Engineering Research Council (NSERC), the Social Sciences and Humanities Research Council (SSHRC), and Mitacs. At this time, the platform connects to the awards databases of CIHR, NSERC and the SSHRC, as well as CFI’s Research Facilities Navigator. In addition, COGNIT.CA provides a catalogue of current licensing opportunities from Canadian post-secondary institutions as well as a listing of patents filed for by Canadian post-secondary researchers and institutions.